2016
DOI: 10.1590/0001-3765201620150228
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects in CGRPergic, nitrergic, and VIPergic myenteric innervation in diabetic rats supplemented with 2% L-glutamine

Abstract: The objective of this study was to investigate the effects of 2% L-glutamine supplementation on myenteric innervation in the ileum of diabetic rats, grouped as follows: normoglycemic (N); normoglycemic supplemented with L-glutamine (NG); diabetic (D); and diabetic supplemented with L-glutamine (DG). The ileums were subjected to immunohistochemical techniques to localize neurons immunoreactive to HuC/D protein (HuC/D-IR) and neuronal nitric oxide synthase enzyme (nNOS-IR) and to analyze varicosities immunoreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Changing the ratio of inhibitory and contractile neurons can lead to impaired nerve‐mediated muscle responses and contribute to the motility dysfunction seen in diabetes . Our results showed decreased nNOS expression in the ileum 8 and 16 weeks after the induction of diabetes, particularly at 16 weeks, which is consistent with previous reports . Results from previous studies regarding the alterations in cholinergic neurons in diabetes are conflicting, possibly because of the different responses of enteric neuronal subpopulations to hyperglycemia and because the same types of nerves that innervate various regions of the GI tract are affected differently .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Changing the ratio of inhibitory and contractile neurons can lead to impaired nerve‐mediated muscle responses and contribute to the motility dysfunction seen in diabetes . Our results showed decreased nNOS expression in the ileum 8 and 16 weeks after the induction of diabetes, particularly at 16 weeks, which is consistent with previous reports . Results from previous studies regarding the alterations in cholinergic neurons in diabetes are conflicting, possibly because of the different responses of enteric neuronal subpopulations to hyperglycemia and because the same types of nerves that innervate various regions of the GI tract are affected differently .…”
Section: Discussionsupporting
confidence: 86%
“…4 Our results showed decreased nNOS expression in the ileum 8 and 16 weeks after the induction of diabetes, particularly at 16 weeks, which is consistent with previous reports. 26,27 Results from previous studies regarding the alterations in cholinergic neurons in diabetes are conflicting, [28][29][30] possibly because of the different responses of enteric neuronal subpopulations to hyperglycemia and because the same types of nerves that innervate various regions of the GI tract are affected differently. 4,28 Our data showed a statistically significant increase in Increasing evidence has confirmed that EGCs are major contributors to the GI complications of diabetes, which provides insight into the role of EGCs in enteric neuropathies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed that the role of Gln in diabetes goes beyond traditional metabolic functions of amino acids. New discoveries of Gln function have been reported, including the role of enhanced endothelial progenitor cell mobilization in diabetic mice [ 37 ], differential effects in calcitonin gene-related peptide-ergic, nitrergic, and vasoactive intestinal polypeptide-ergic myenteric innervation in diabetic rats [ 38 ], as well as the effect on adhesion molecule expression and oxidative stress in mice with diabetes [ 39 ]. Similarly, our results show that Gln has a beneficial hypoglycemic effect on L6 cells through the PI3K/AKT/GLUT4 signaling pathway, and the hypoglycemic effect of insulin was enhanced in the presence of Gln.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of effect in this plexus has been previously reported during the development of the diabetic enteric neuropathy [ 33 ]. Another recent study also revealed that l -glutamine exerted a differential neuroprotective effect in experimental diabetes that depend on the type of neurotransmitter analyzed [ 63 ].…”
Section: Discussionmentioning
confidence: 99%